Albyumkaniki qualitative analysis and its impact on the development of some of the skills of tennis - Star, Hasnaa (Journal of Physical Education, 2008)
The research aims at identifying the effect of biomechanical analysis using observation on the development of the performance of forehand ,bakhand and the servci on players who have difficulty in learning this skills. The subject of the research were (20) third year students of the college of physical education/university of Baghdad. The researcher excluded all players who are good in performing this skills. The researcher Proceduer tests to forhand ,bakhand and speed serv . and given learning mechanical feedbak after limitation important mechanchal mistakes from perform skills by observer. Finally he conducted the proper statistical methods to find the results